Somatic Complaints Are Significantly Associated with Chronic Uninvestigated Dyspepsia and Its Symptoms: A Large Cross-sectional Population Based Study - Heidari, Zahra (J Neurogastroenterol Motil, 2017)
BACKGROUND/AIMS: Somatization may influence persistence and severity of symptoms in gastrointestinal diseases. Some studies suggest that somatization is associated with chronic uninvestigated dyspepsia (CUD); however, the association is unclear. We aimed to determine the association between the profiles of somatic complaints with CUD and its symptoms. METHODS: In a cross-sectional study conducted on 4763 Iranian adults, somatic complaints were assessed using a comprehensive 31-items questionnaire. Patients with CUD were identified by the Rome III diagnostic criteria. Profiles of somatic complaints were derived from factor analysis. Logistic regression analysis was used to assess the relationship between extracted profiles with CUD and its symptoms. RESULTS: CUD, bothersome postprandial fullness, early satiation, and epigastric pain or burning was identified in 723 (15.2%), 384 (8.1%), 302 (6.3%), and 371 (7.8%) of the study population. The frequency of all 31 somatic complaints was significantly higher in patients with CUD compared with controls (P < 0.001), and the most frequent was severe fatigue (45.1%). The profiles of somatic complaints were extracted in 4 domains, including “psychological”, “gastrointestinal”, “neuro-skeletal”, and “pharyngeal-respiratory”. The psychological (OR, 1.49; 95% CI, 1.44–1.54), gastrointestinal (OR, 2.22; 95% CI, 2.09–2.37), neuro-skeletal (OR, 1.52; 95% CI, 1.44–1.59), and pharyngeal-respiratory (OR, 2.09; 95% CI, 1.94–2.25) profiles were significantly associated with greater odds of CUD. CONCLUSIONS: CUD and its symptoms are strongly associated with higher levels of somatic complaints and their related extracted profiles. This perhaps explains that why it can be difficult to treat, however further prospective investigations are required to confirm these associations.